Al-Khilafah Al-Islamiyah fi Muwajihati Al-‘Ilmaniyah: Dirasah Maudhu’iyah fi Tafsir Fi Dzilali Al-Qur’an - Nindhya Ayomi Delahara; Asif Trisnani (Universitas Darussalam Gontor, 2021)
This article aims to discuss the interpretation of the Khilafah as the opposition to secularization of politics according Sayyid Quthb. The proponents of secularism assume that state law cannot be put together with the religious law because of the absence of a relation. In addition, secularism tries to destroy the Khilafah Islamiyyah and the Sultanate of Ottoman Turkey in the 19th while the sultanate was led by Musthofa Kemal who attempts to affect the country and to destroy Islam as religion in the country. Rasullullah as the first khalifah of Islam has shown that a country can be built by following the Qur’an and Sunnah. That can be proven with the formation of the state in Medina and the Medina Charter as the law of this country. Based on this background, the Author Attempts to study thematically the problem of Khilafah in the Qur’an according to Sayyid Quthb in his Tafsir in order to discover how he opposes secularism through proposing his concept of Khilafah. In addition, the Author also uses Socio literature approach to describe sociological aspect of the interpretation of the Qur’an pertaining to the problem of Khilafah. Sayyid Quthb suggested that state law cannot be separated from Islamic law. It was because that appointing man to be a khalifah in the earth has been declared initially before the creating of Adam that has been equipped with the intellect the benefit of which is for scrutinizing all laws of Allah, having been recorded in the verses of Qur’an. This law will help human being to perform their obligations as khilafatu al-ardhi Therefore, if the state keeps the laws of Islam instead of the laws of country, it will cause muslim community keeps away from the sharia and put forward their thought and passion.